أثر استخدام البوليمير العضوي Carboxyl Methyl Cellulose على ثباتية البناء ودرجة التحبب لثلاث ترب مختلفة - بركات, منى (Latakia University Journal -Biological Sciences Series, 2019)
من خلال عملية تحضين لثلاثة أنواع من الترب المختلفة في محتواها من الطين فقد احتوت التربة الأولى على 53% طين واحتوت الثانية على 25% أما الثالثة فكان محتواها 28% مع ثلاثة تراكيز من مركب الـ Carboxyl Methyl Cellulose (CMC)البوليميري العضوي وهي 1% ، 2% ، 3% وذلك بواقع ثلاثة مكررات لكل معاملة. بعد التجفيف الهوائي تم تحديد كل من درجة التحبب ونسبة التفكك للترب الثلاث أما بالنسبة لثباتية البنية فقد درس في تربتين فقط وهما التربة الأولى والتربة الثانية . أهم ما توصلت إليه الدراسة وجود زيادة معنوية في درجة التحبب في الترب الثلاث مقارنة بالشاهد وتتناسب هذه الزيادة إيجابياً مع ارتفاع تركيز البوليمير المضاف وبالمقابل فقد انخفضت نسبة التفكك وكانت علاقتها سلبية ، فقد انخفضت نسبة التفكك بازدياد تركيز البوليمير المضاف. لقد ظهر واضحاً تأثير محتوى التربة من الطين في درجة تحبب التربة فقد ازدادت نسبة التحبب بازدياد محتوى التربة من الطين . أما بالنسبة لثباتية البناء فقد تحسنت باستخدام البوليمير في كلا التربتين المستخدمتين وكانت هذه الزيادة أكثر وضوحاً في الترب ذات المحتوى الأعلى من الطين وهي التربة الأولى . From an incubation study of three soil variables in their clay content, 53 % for the first, 25% for the second and 28 % for the third. These soils were incubated with different concentrations of Carboxyl Methyl Cellulose (CMC) these concentrations were 1%, 2% and 3% of the soil with three replicates for each treatment. After air drying the aggregation, dissociation degrees were determined for the three soils, whereas the structured stability of only the first and second soils was studied.. The most important result of this study was, a significant increase in aggregation degree in the three soils in comparasion with controls. This increase is positively related to clay content of soils and to the increase of added concentration of the polymer for each soil. Regarding the degree of dissociation, there was a decrease when the polymer concentration was increased. There was also a clear influence of clay content on the degree of aggregation, it increased when the clay content increased. Regarding the structurale stability, it was improved with the use of polymer in the two used soils, this incease was more pronounced in the first soil which has a higher clay content.